Association between hypertriglyceridemic waist phenotype and Diabetes mellitus in adults: a case-control study (Research, Society and Development, 2022)
Diabetes mellitus (DM) is considered a major public health problem. Studies in several countries points to the usefulness of evaluating the hypertriglyceridemic waist (HTC) phenotype to predict the risk of the disease. Aim: This study aimed to evaluate the association between the HTC phenotype and DM type 2 in Dourados, MS, Brazil. Methods: This is a case-control study nested within a population-based cross-sectional survey with multiple-stage sampling, carried out in 2016. The sample included 293 adults aged 20 to 59 years, of which 56 were cases and 237 controls. The cases were those with fasting blood glucose ≥ 126mg/dL and who reported that “a doctor or health professional has already said that “Do you have high blood sugar?” Controls were drawn from the other interviewees, without DM. Individuals with waist circumference (WC) were considered to have the HTC phenotype: ≥ 80 cm for women and ≥ 90 cm for men, combined with hypertriglyceridemia (TG) ≥ 150 mg/dL. The variables gender, age, education, socioeconomic status, smoking, alcohol consumption, physical activity and body mass index were investigated. Chi-Square Test, Fisher's Exact Test and Unconditional Logistic Regression were used for data analysis. Results: The HTC phenotype was positively associated with DM: 2.08, 95%CI: 1.04-4.12, after adjusting for covariates. Conclusion: The study suggests that the HTC phenotype may be useful as an approach in the identification of DM.